2004
DOI: 10.1038/sj.cdd.4401451
|View full text |Cite
|
Sign up to set email alerts
|

Role of hyperhomocysteinemia in endothelial dysfunction and atherothrombotic disease

Abstract: Hyperhomocysteinemia (HHcy) is an independent risk factor for cardiovascular disease, including ischemic heart disease, stroke, and peripheral vascular disease. Mutations in the enzymes responsible for homocysteine metabolism, particularly cystathionine b-synthase (CBS) or 5,10-methylenetetrahydrofolate reductase (MTHFR), result in severe forms of HHcy. Additionally, nutritional deficiencies in B vitamin cofactors required for homocysteine metabolism, including folic acid, vitamin B6 (pyridoxal phosphate), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
233
1
17

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(260 citation statements)
references
References 121 publications
(169 reference statements)
6
233
1
17
Order By: Relevance
“…The effects of NaHS and L-Cys ( Fig. 7) were markedly inhibited by both INDO (1 μM,°°°P < 0.001) and AACOCF 3 (1 μM; ### P < 0.001). In addition, NaHS (100 μM) and L-Cys (100 μM) by themselves did not affect TxB 2 production (Fig.…”
Section: Figmentioning
confidence: 95%
See 1 more Smart Citation
“…The effects of NaHS and L-Cys ( Fig. 7) were markedly inhibited by both INDO (1 μM,°°°P < 0.001) and AACOCF 3 (1 μM; ### P < 0.001). In addition, NaHS (100 μM) and L-Cys (100 μM) by themselves did not affect TxB 2 production (Fig.…”
Section: Figmentioning
confidence: 95%
“…H 2 S gaseous transmitter | urinary 11-dehydro-TXB2 | cardiovascular events | DL-propargylglycine | aminooxyacetic acid H yperhomocysteinemia (HHcy) is a risk factor for neurovascular and cardiovascular disease associated with endothelial dysfunction and accelerated atherosclerosis (1)(2)(3). Many clinical and epidemiological studies have demonstrated a positive correlation between homocysteine (Hcy) plasma levels and cardiovascular disorders (4,5), leading to the general conclusion that Hcy is a prothrombotic factor (6)(7)(8).…”
mentioning
confidence: 99%
“…It has also been reported that there is a link between XBP1 and human disease (16,17). Although ER stress is reported to be involved in atherosclerosis (18)(19)(20)(21)(22), the role of XBP1 in vascular disease has not been examined in detail. In the present study, we demonstrated that disturbed flow induces XBP1 splicing and sustained activation that led to EC apoptosis and the formation of atherosclerotic lesion in ApoE Ϫ/Ϫ mice.…”
mentioning
confidence: 99%
“…Although some studies found evidence of an association between the polymorphic MTHFR 677T allele and vascular diseases, carotid atherosclerosis, occlusive arterial disease and myocardial infarction [15][16][17][30][31][32] , others did not confirm these hypotheses 11,33 . A b o u t 4 0 % o f p a t i e n t s w i t h C A D p r e s e n t hyperhomocysteinemia 34 . In our study, 49.7% of the patients with CAD and 45.2% of the controls showed Hcy concentrations >15 µmol/L, and this difference was not significant.…”
Section: Discussionmentioning
confidence: 99%